Physical inactivity as a determinant of obesity - Saris, Wim (Henry Stewart Talks, 2007)
Energy balance, Food intake, Fat stores, Trends in physical activity and energy intake, Components of physical activity, Physical activity and weight (re-)gain, Prospective studies, Evolutionary perspective, Doubly labelled water studies, Energy costs of activities, Role of exercise intensity, Guidelines for physical activity